Comparative Marshall Performance of Asphalt Concrete and Stone Mastic Asphalt Mixtures for Taxiway Pavements Based on FAA Specifications - Alifah Widya Rochmah; Ervina Ahyudanari; Budi Rahardjo; Istiar; Viorentika Vigrid Yuniar Dirgan Putri (Jurnal Teknologi dan Manajemen Industri Terapan, 2026)
Taxiway flexible pavements are subjected to high shear stresses from slow-moving aircraft with large wheel configurations, making mixture stability and resistance to permanent deformation critical performance requirements. Asphalt Concrete (AC) and Stone Mastic Asphalt (SMA) are commonly used wearing course mixtures; however, their performance characteristics under taxiway loading conditions may differ significantly. This study presents a comparative evaluation of the Marshall performance of AC and SMA mixtures designed in accordance with Federal Aviation Administration (FAA) specifications for taxiway pavements. Laboratory experiments were conducted using the Marshall mix design method to determine key parameters, including stability, flow, Marshall Quotient (MQ), Voids in Mix (VIM), Voids in Mineral Aggregate (VMA), Voids Filled with Asphalt (VFA), and Optimum Asphalt Content (OAC). The results indicate that the AC mixture exhibits higher average Marshall stability, reflecting superior load-bearing capacity, whereas the SMA mixture demonstrates lower flow values, indicating greater resistance to permanent deformation. The OAC of the SMA mixture is higher than that of the AC mixture due to its stone-on-stone aggregate structure and larger VMA. These findings highlight the trade-off between structural stiffness and deformation resistance in selecting wearing course mixtures for taxiway pavements and provide technical insights for mixture selection based on FAA performance requirements.